Future-oriented technology analysis: strategic intelligence for an innovative economy - Cagnin, Cristiano (Springer, 2008)
The application of foresight to address the challenges of uncertainty and rapid change has grown dramatically in the past decade. In that period, the techniques have been greatly refined and the scope has been broadened to encompass future-oriented technology analysis (FTA) and more recently, the concept and practice of strategic intelligence. FTA addresses directly the longer-term future through the active and continuous development of visions, and pathways to realise these visions. It is increasingly seen as a valuable management and policy tool complementing, and extending further into the